Checklist of the earthworm fauna (Oligochaeta: Lumbricidae) of Uzbekistan - IKRAM ABDULLAEV; MADINA BEKCHANOVA; LOLA GANDJAEVA; BAKHTIYOR KHOLMATOV; ALIMARDAN RAХMATULLAYEV; ZOKIR TAJIYEV; KHAXRAMON RAZZAKOV; ZAFARBEK MATYAKUBOV; MANZURA DOSCHANOVA; RASUL RUZMETOV (Society for Indonesian Biodiversity, 2023)
Abstract. Abdullaev I, Bekchanova M, Gandjaeva L, Kholmatov B, Raxmatullayev A, Tajiyev Z, Razzakov K, Matyakubov Z, Doschanova M, Ruzmetov R. 2023. Checklist of the earthworm fauna of Uzbekistan (Oligochaeta: Lumbricidae). Biodiversitas 24: 4392-4401. This article presents a checklist of the earthworm fauna (Lumbricidae) of Uzbekistan based on published records and the authors' data. This is the first checklist for Uzbekistan, which contains complete information on the ecological category, habitat, type of distribution and distribution of 28 species of earthworms in 4 regions of Uzbekistan. The currently known, based on our research, earthworm fauna of Uzbekistan, includes 23 species, 5 subspecies belonging to 9 genera. Of them, 3 species (Perelia persiana, Perelia turcmenica, Lumbricus rubellus) are new to Uzbekistan. Perelia is the species-richest genus (12 species). These earthworms are distributed Kyzylkum desert region along river banks, in the mountainous regions of Pomiro Alai and Tien Shan biogeographic region, which is mostly covered with forest or autochthonous flora. The earthworm fauna is more diverse in forests of the northern and in the mountains of the southern parts of Uzbekistan. Literature data and our present study showed that there are no earthworms in the Ustyurt Plateau, due to the fact that the soils of the Ustyurt Plateau are gypsum, saline, and infertile.